Public relation sebagai manajemen krisis dalam membangun kembali kepercayaan nasabah pasca serangan siber bank BSI - Adinugroho, Muhammad Bayu (Maliki Interdisciplinary Journal, 2025)
In 2020, the government announced the merger of Bank Syariah Mandiri, BNI Syariah, and BRI Syariah to become Bank Syariah Indonesia (BSI). In May 2023, BSI experienced a cyberattack by the LockBit 3.0 group, causing banking services to be paralyzed for five days and customer data leaks. This study uses the SSCT theory from Coombs & Holladay. First, BSI implements a deny strategy by reducing the impact of the crisis. Second, the diminish strategy is seen in apologies to customers and explanations of system maintenance steps. Third, the bolstering strategy is carried out by reminding customers of potential fraud. Public relations (PR) plays an important role as a communication bridge between BSI and customers, conveying accurate information and alleviating public concerns.